A case of suspected teratogenic holoprosencephaly. Issue 2 (April 1985) - Stabile, M; Bianco, A; Iannuzzi, S; Buonocore, M C; Ventruto, V
Abstract : A case of holoprosencephaly is reported in which the mother was prescribed high doses of oestroprogestins during the first 5 months of the pregnancy. Investigation of the family failed to reveal any sign of physical abnormality. A normal karyotype was detected in the proband. The authors suggest that this case may shed some light on the normal and abnormal way in which embryonic fields develop.